The Evaluation of Arm’s Lenght Principle and Transfer Pricing Method on the Application of Income Tax Payable (Case Study of PT. ABC) - Dewi Raraswati Dayaningrum; Hasan Rachmany; Eliza Eliza (LPPM-STPI, 2021)
Transfer pricing is a sensitive issue in the business world and the global economy, expecially taxation. Transfer pricing activities carried out by multinational companies affect the level of state tax revenues, either directly or indirectly. The purpose of the research conducted by the author is to determine the suitability of the transfer price method to the calculation of Income Tax Payable related to transfer pricing transaction. The research was conducted in one of companies engaged in information technology services & consultants in Indonesia. From the results of study, it can be concluded that in terms of the use of the transfer price method, in accordance with the arm's length principle. However, in relation to the application of the transfer price method, it does not meet the general application practices according to the OECD Guidelines, which causes the calculation of Income Tax Payable by Corporate Taxpayers to be inconsistent with regard to transfer pricing transactions.